The normal neuroendocrine cells of the upper gastrointestinal tract lack E-cadherin. (August 2014) - Waldum, Helge L.; Ringnes, Eva; Nordbø, Helene; Sørdal, Øystein; Nordrum, Ivar S.; Hauso, Øyvind
Abstract Objective. E-cadherin plays a crucial role in the adhesion between epithelial cells and thus epithelial integrity. Moreover, germline mutations in the E-cadherin gene (CDH1) causing loss of E-cadherin function (adhesion) leads to hereditary gastric cancer of the diffuse type, according to Laurén. Even sporadic gastric carcinomas of the diffuse type often lose E-cadherin expression due to mutations. Lack of E-cadherin has been recorded at an early phase in such carcinomas. For 25 years, we have provided evidence for neuroendocrine (NE) cell origin of gastric carcinomas of diffuse type. The present study was, therefore, done to examine whether normal NE cells in the gastrointestinal tract express E-cadherin or not. Methods. During upper gastrointestinal endoscopy, biopsies were taken from normal oxyntic mucosa, gastric carcinoids, gastric carcinomas, and from normal duodenal mucosa. Tissues were examined by immunohistochemistry (IHC) using antibodies toward chromogranin A, synaptophysin, and E-cadherin. Isolated mucosal cells were prepared from biopsies of normal mucosa and examined by antibodies against the same markers by immunofluorescence. Results. Normal gastrointestinal NE cells did not express E-cadherin as assessed by IHC or immunocytochemistry. No expression of E-cadherin was found on tumor cells from gastric carcinoids or cancer of diffuse type examined by IHC. Conclusion. Our findings, which are in contrast to some previous studies, may explain why there is a discrepancy between lack of atypia and malignant biological behavior of such tumors. Since they normally lack the adhesion molecule E-cadherin, reflected in their spread occurrence, only minor changes may result in malignant behavior.